OSTEOGENESIS DAN TUMBUH-KEMBANG SKELET KRANIOFASIAL MANUSIA - Sarworini Bagio Budiardjo (Faculty of Dentistry, Universitas Indonesia, 2015)
Osteogenesis depends on the original cells, which are indirect or endochondral osteogenesis, and direct or intramembranous osteogenesis. The skeletal of craniofacial consist of bones, group of bones, and cartilages. The function of the skeletal of craniofacial is supported and covered the part of soft tissues in the calvaria. Basically the skeletal ontogenesis of craniofacial same to the other bones which are deposition-resorption, growth field, remodeling, and growth movement. The skeletal osteogenesis of craniofacial controlled by growth sites and growth centers.